1984
DOI: 10.5014/ajot.38.8.529
|View full text |Cite
|
Sign up to set email alerts
|

Denial: Implications of a Pilot Study on Activity Level Related to Sexual Competence in Burned Adults

Abstract: The purpose of this pilot study was to explore the effect of disfigurement on sexual competence and the relationship between self-reported activity level and sexual competence in burn-disfigured adults. Because of a small sample size and methodological limitations, findings were intended to be informative for planning further research rather than definitive. Results showed a strong positive correlation between activity level and sexual competence. Additional findings showed surprisingly high activity levels re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1986
1986
2012
2012

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Although there is an abundance of general literature on sexuality and disability, relatively little has been published on this topic in the occupational therapy literature in the past 10 years. There are only two studies (Cooper-Fraps, 1984;Sidman, 1977) in addition to those already mentioned.…”
mentioning
confidence: 99%
“…Although there is an abundance of general literature on sexuality and disability, relatively little has been published on this topic in the occupational therapy literature in the past 10 years. There are only two studies (Cooper-Fraps, 1984;Sidman, 1977) in addition to those already mentioned.…”
mentioning
confidence: 99%
“…However, research has suggested that negative societal attitudes still exist (Chandani et al 1989). Also, some authors (Cooper-Fraps andYerxa 1984, Brown 1988) have reported asexualising attitudes by health professionals.…”
Section: The Client As a Sexual Beingmentioning
confidence: 94%